2014
DOI: 10.1177/089875641403100403
|View full text |Cite
|
Sign up to set email alerts
|

Nomenclature and Classification of Odontogenic Tumors — Part II: Clarification of Specific Nomenclature

Abstract: Accurate identification of odontogenic tumors is critical for productive communication and an important foundation for useful comparative epidemiologic studies of odontogenic tumors in both domestic animals and humans. This manuscript illuminates the subject of veterinary odontogenic tumor nomenclature and will serve as a foundation for future updates in nomenclature and classification of odontogenic tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 61 publications
0
45
0
Order By: Relevance
“…The nomenclature and diagnostic procedures to identify proliferative odontogenic lesions properly in both human and veterinary literature are complicated and varied due to the inherent complexities in the tissues involved, and the differences in behaviour and origin of these lesions within and between different species (Kramer et al . ; Bell and Soukup ). Although classification systems in animals have progressed since the realisation that several odontogenic entities and their biological behaviour are unique to animals, reports in the veterinary and equine literature are rife with morphological, aetiological and prognostic discrepancies, and controversy still exists regarding the best way to classify these lesions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The nomenclature and diagnostic procedures to identify proliferative odontogenic lesions properly in both human and veterinary literature are complicated and varied due to the inherent complexities in the tissues involved, and the differences in behaviour and origin of these lesions within and between different species (Kramer et al . ; Bell and Soukup ). Although classification systems in animals have progressed since the realisation that several odontogenic entities and their biological behaviour are unique to animals, reports in the veterinary and equine literature are rife with morphological, aetiological and prognostic discrepancies, and controversy still exists regarding the best way to classify these lesions.…”
Section: Introductionmentioning
confidence: 98%
“…Of note in the veterinary literature, ‘cementoma’ has been found to refer to both a true neoplastic condition as well as a dysplastic or hyperplastic lesion. The 3 most likely diagnoses for lesions referred to as ‘cementoma’ in the veterinary literature are true cementoma/cementoblastoma, periapical cemento‐osseous dysplasia, and hypercementosis (Bell and Soukup ).…”
Section: Introductionmentioning
confidence: 99%
“…The amyloid-producing odontogenic tumor (APOT) is an uncommon odontogenic neoplasm in dogs and cats. Based on previous case reports, it occurs most commonly in older dogs with a predilection for small breeds, but large clinicopathologic studies are lacking ( 1 6 ). APOT has also been reported in a goat, prairie dog, and Bengal tiger ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Histologically, APOTs are characterized by the presence of the odontogenic epithelium with extracellular deposition of amyloid-like material ( 1 6 ). Previous investigators have shown that the material has positive immunolabeling targeting ameloblast proteins (amelogenin, sheathlin, and ameloblastin) and suggested that this tumor would be better referred to as amyloid-producing ameloblastoma ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation